2017
DOI: 10.1016/j.bbamcr.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation and reprogramming: Overview of the processes, their similarities and differences

Abstract: Reprogramming, or generation of induced pluripotent stem (iPS) cells (functionally similar to embryonic stem cells or ES cells) by the use of transcription factors (typically: Oct3/4, Sox2, c-Myc, Klf4) called "Yamanaka factors" (OSKM), has revolutionized regenerative medicine. However, factors used to induce stemness are also overexpressed in cancer. Both, ES cells and iPS cells cause teratoma formation when injected to tissues. This raises a safety concern for therapies based on iPS derivates. Transdifferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 146 publications
1
61
0
3
Order By: Relevance
“…Our results highlight the need for tight control of proliferation and terminal differentiation. This underscores the importance of emerging approaches such as the incorporation of a suicide gene for proliferating cells into the graft 86 , selection of a suitable progenitor population, expressing specific surface ventral midbrain markers 88 , or by trans-differentiation of more mature cells 89 . It also underpins the importance of approaches such as the one investigated here that enable prolonged maturation prior to implantation, offering the possibility of later quality control points.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight the need for tight control of proliferation and terminal differentiation. This underscores the importance of emerging approaches such as the incorporation of a suicide gene for proliferating cells into the graft 86 , selection of a suitable progenitor population, expressing specific surface ventral midbrain markers 88 , or by trans-differentiation of more mature cells 89 . It also underpins the importance of approaches such as the one investigated here that enable prolonged maturation prior to implantation, offering the possibility of later quality control points.…”
Section: Discussionmentioning
confidence: 99%
“…Transdifferentiation is known in many species including vertebrates (Cieslar-Pobuda et al, 2017;Reid and Tursun, 2018), but in the blood cell system transdifferentiation has for the most part only been studied in vitro and by experimental manipulations. For example, C/EBP (CCAAT/enhancerbinding protein) transcription factors drive transdifferentiation of vertebrate B cells into macrophages (Xie et al, 2004) (Di Tullio et al, 2011), force B lymphoma and leukemia cell lines to transdifferentiate into macrophages (Rapino et al, 2013), and facilitate B cell transdifferentiation to Granulocyte-Macrophage Precursors (Cirovic et al, 2017).…”
Section: A Drosophila Model Of Blood Cell Transdifferentiationmentioning
confidence: 99%
“…In contrast to previous observations, Bar-nur et al [43] surprisingly showed that BSKM was actually able to generate iPSC-like colonies and hallmarked by activation of endogenous pluripotency genes Oct4, Nanog, and Zfp42, in both embryonic stem cell and NSC media. In conclusion, identification of potential pluripotency intermediates during reprogramming procedures is important to distinguish between iPSC-coupled mechanisms and true transdifferentiation [40,43,44]. Another study used two lineage tracing systems, Nanog-CreER and Oct4-CreER, to follow the transdifferentiation of mouse embryonic fibroblasts (MEFs) toward cardiomyocytes or iNSCs [44].…”
Section: Molecular Mechanisms Regulating Direct Conversion Of Somaticmentioning
confidence: 99%
“…Induced neural stem cells are generated through direct conversion, a process in which cells acquire the expression of NSC markers in a stepwise fashion, theoretically without passing through a pluripotent state [40]. However, most protocols for iNSC generation involve the Yamanaka factors OSKM [11,13,25,26,41,42], suggesting that cells undergo a transient pluripotent state during the reprogramming process.…”
Section: Molecular Mechanisms Regulating Direct Conversion Of Somaticmentioning
confidence: 99%
See 1 more Smart Citation